PENINGKATAN MODEL ASOSIASI TOKO IKHSAN MENGGUNAKAN ALGORITMA FP-GROWTH - Hanafi, Muhammad Salman; Nurdiawan, Odi; Basysyar, Fadhil Muhammad (Universitas Lampung, 2025)
FP-Growth, Data Mining, Purchase Patterns, Marketing Strategies, Retail Store.